Suboptimal Immune Reconstitution among HIV-Infected Saudi Patients following Successful Antiretroviral Treatment. (10th January 2019) - Al-Majid, Fahad; Shakoor, Zahid; Barry, Mazin
Abstract : Background and Objectives . Variations in immune reconstitution following antiretroviral treatment (ART) among HIV patients have previously been observed. This study aims at assessing immune reconstitution after successful ART among HIV-infected Saudi patients. Methods . This retrospective study of 240 HIV-infected patients was performed between May 2010 and June 2015 in the HIV center at King Saud Hospital, Riyadh. Data were extracted for CD4, CD8 cell, and CD3/HLA-DR counts along with the viral load from patient records before and after four years of successful ART. The inclusion criterion was patients with CD4 reconstitution of either equal to or more than 400 cells/mm 3 with an undetectable HIV viral load following ART. Based on their presentation, the HIV patients were grouped into early treatment (ET) and delayed treatment (DT) groups with CD4 counts of 200–350 cells/mm 3 and less than 200 cells/mm 3, respectively. Findings . The pretreatment CD8+ counts of median 865 cells/mm 3 (interquartile range (IQR) 774–1072) in the DT group declined to median 753 cells/mm 3 (IQR 574–987;p < 0.0001 ). Moreover, there was a decline in CD8 counts from 703 cells/mm 3 (IQR 655–747) to 620 cells/mm 3 (IQR 563–645;p < 0.04 ) in the ET group after four years of successful ART. Pretreatment activation marker (CD3/HLA-DR+) expression of median 29% in the DT group declined to 22% and in the ET group from a median of 23% to 19% after treatment. The CD4/CD8 ratio in the DT group increased from 0.14 (IQR 0.09–0.88) to 0.71 (IQR 0.54–0.9) and from 0.42 (IQR 0.35–0.55) to 0.87 (IQR 0.71–0.98) in the ET group. Conclusion . Immune reconstitution after successful ART among HIV-infected Saudi patients was associated with a CD8 T-cell population expansion with a suboptimal CD4/CD8 ratio and persistent immune activation. Early initiation of ART appears to favorably influence the CD4/CD8 ratio.